PENGARUH WORK OVERLOAD DAN INTIMIDASI TERHADAP KINERJA KARYAWAN ACCOUNT OFFICER PT. BANK ACEH SYARIAH - Said Kahlil Gibran; Irma Suryani (Departemen Manajemen, Universitas Syiah Kuala, 2019)
AbstractThis study aims to examine the effect of Work Overload and Intimidation on Bank Aceh Account Officer Employee Performance. The sampling method in this study used the Proposional Stratifield Sampling technique in which respondents were taken based on certain class strata. A sample of 75 respondents and the data analysis method used was multiple regression analysis. The results of the study show that partially and simultaneously Work Overload and Intimidation together have a negative and significant influence on Bank Aceh Account Officer Employee Performance.Keywords Work Overload, Intimidation, Employee Performance